2019
DOI: 10.2169/internalmedicine.2875-19
|View full text |Cite
|
Sign up to set email alerts
|

A Long-term Response to Nivolumab in a Case of PD-L1-negative Lung Adenocarcinoma with an <i>EGFR</i> Mutation and Surrounding PD-L1-positive Tumor-associated Macrophages

Abstract: Anti-programmed cell death 1 (PD-1) antibodies have poor efficacy in epidermal growth factor receptor (EGFR)-mutated lung cancer. We herein report a 72-year-old man with programmed cell death-ligand 1 (PD-L1)-negative lung adenocarcinoma harboring an EGFR mutation that responded to nivolumab for more than 2 years. A pathological examination revealed infiltration of CD8-positive lymphocytes and macrophages expressing CD68, CD206, and PD-L1 into the PD-L1-negative tumor; CD206 expression is a marker of immunosup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 23 publications
2
12
0
Order By: Relevance
“…The CD68-positive macrophages were also positive for CD163 (M2-like macrophage), a marker for immunosuppressive tumor-associated macrophages (TAMs). Considering the availability of similar reports in the past [ 26 ], the excellent therapeutic effects observed in our case can be attributed to the following scenarios: (1) TAMs suppressed CD8-positive lymphocytes, (2) nivolumab inhibited the negative interaction of M2 macrophages, and (3) CD8-positive lymphocytes were released and attacked the tumor. However, given that this is a case report, future case series are needed to validate such mechanisms.…”
Section: Discussionsupporting
confidence: 56%
“…The CD68-positive macrophages were also positive for CD163 (M2-like macrophage), a marker for immunosuppressive tumor-associated macrophages (TAMs). Considering the availability of similar reports in the past [ 26 ], the excellent therapeutic effects observed in our case can be attributed to the following scenarios: (1) TAMs suppressed CD8-positive lymphocytes, (2) nivolumab inhibited the negative interaction of M2 macrophages, and (3) CD8-positive lymphocytes were released and attacked the tumor. However, given that this is a case report, future case series are needed to validate such mechanisms.…”
Section: Discussionsupporting
confidence: 56%
“…Recent case report is available that suggested that TAMs in lung cancer can be a predictor of a positive response to anti-PD-1 antibodies (nivolumab) in patents with EGFR-mutated lung cancer (197). In this case report a 72-year old male patient with lung adenocarcinoma (cT1bN2M0, cStage IIIA) was harboring anEGFRexon19 deletion.…”
Section: Tams and Lung Cancer Treatmentmentioning
confidence: 87%
“…After seven cycles of nivolumab administration, the patient has continued treatment with nivolumab for more than two years with no evidence of tumor regrowth or serious immunerelated adverse events (197). TAMs were analyzed in lung tumor by IHC, and CD68, CD206 and PD-L1 expression was detected (197). However, this study does not provide any evidence for the dynamic changes of TAM amounts or phenotypes in primary tumor and metastatic sites and also during different chemotherapy approaches.…”
Section: Tams and Lung Cancer Treatmentmentioning
confidence: 91%
See 1 more Smart Citation
“…Previous studies reported about the potential indispensable role of PD-L1 expressed by non-tumor cells on PD-L1 blockade-mediated tumor elimination in murine tumor models and the correlation between PD-L1-positive macrophages and the positive effects of anti-PD-L1 and anti-PD-1 antibodies in lung cancers and melanoma. [45][46][47] Our study might offer a clue to select intratumor PD-L1positive macrophages as promising biomarker for the use of checkpoint inhibitors.…”
Section: Open Accessmentioning
confidence: 94%